Design, construction, and validation of a portable one-dimensional force platform - Major, J. A.; Sands, W. A.; McNeal, J. R.; Paine, D. D.; Kipp, R. (The Journal of Strength and Conditioning Research, 1998)
The purpose of this project was to design, build, and validate a portable force platform (PFP) for recording instantaneous vertical ground reaction forces in vertical jumps. The platform was constructed of 2 steel plates each 70 cm x 70 cm and was calibrated with 3 sets of known weights in 9 positions on the PFP. A 3 x 9 factorial ANOVA (weight x position) was calculated on 25 raw samples per region and per weight to determine if regions of the PFP responded differently. The only statistically significant difference was the main effect for weight. PFP linearity was determined by correlating 17 known weights and voltage outputs. The PFP was placed on top of an AMTIª force platform and vertical jumps were performed while sampling from both platforms simultaneously at 500 Hz. The natural frequency of the PFP was approximately 100 Hz. The PFP appears to be a simple, inexpensive, and accurate way to measure vertical component force in vertical jumps.